(untitled) (Dermatology Reports, 2023)
Dear Editor, Microwaves are one of the most recent non-invasive fat reduction technologies to emerge. Onda system (DEKA M.E.L.A, Florence, Italy) is an innovative microwave platform that takes advantage of microwaves’ specific biological interaction with subcutaneous fat cells. It comes with two handpieces for selectively concentrating microwave heating in both deep and superficial subcutaneous tissues...